2016
DOI: 10.17533/udea.rccp.v29n1a06
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin resistance of three Rhipicephalus microplus populations using the larval immersion test

Abstract: SummaryBackground: in Colombia, the control of tick infestation in cattle is almost exclusively performed with chemical acaricides. It is important to determine the degree of resistance of Riphicephalus microplus field populations to ivermectins (IVM) as the first step to design strategies to increase the useful life of acaricides and decrease the reliance on chemical controls. Objective: to test the degree of resistance to IVM. Methods: three cattle farms in Antioquia (Colombia) where IVM had previously faile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 11 publications
0
12
0
2
Order By: Relevance
“…microplus que no responden a los acaricidas convencionales. Por ejemplo, en el caso de Antioquia, los estudios in vivo e in vitro en algunos municipios han mostrado que efectivamente existe un problema de resistencia a la mayoría de acaricidas comerciales Puerta et al, 2015;Villar et al, 2016). Para demostrar que se trata de una resistencia innata y no de una mala aplicación o preparación de los productos, se han realizado pruebas in vitro recomendadas por la FAO (2004); simultáneamente se han hecho estudios de campo empleando las guías recomendadas por la Asociación Mundial para el Avance de la Parasitología (Holdsworth et al, 2006).…”
Section: Medicina Veterinaria Y Zootecniaunclassified
“…microplus que no responden a los acaricidas convencionales. Por ejemplo, en el caso de Antioquia, los estudios in vivo e in vitro en algunos municipios han mostrado que efectivamente existe un problema de resistencia a la mayoría de acaricidas comerciales Puerta et al, 2015;Villar et al, 2016). Para demostrar que se trata de una resistencia innata y no de una mala aplicación o preparación de los productos, se han realizado pruebas in vitro recomendadas por la FAO (2004); simultáneamente se han hecho estudios de campo empleando las guías recomendadas por la Asociación Mundial para el Avance de la Parasitología (Holdsworth et al, 2006).…”
Section: Medicina Veterinaria Y Zootecniaunclassified
“…Two methods of acaricide resistance development by ticks are known; one is metabolic resistance and the other is target site insensitivity (Diaz, 2012;de Oliveira Souza Higa et al, 2015). In Colombia, there are reports of resistance to acaricides including organochlorines, formamidines, organophosphates, synthetic pyrethroids, and ivermectin (Benavides et al, 2000;Abbas et al, 2014;Araque et al, 2014;Villar et al, 2016). Information gathered in this study regarding estimated prevalence of ticks, degree of tick infestation, types of acaricide used and frequency of acaricide application (Table 1) suggest there is acaricide resistance in the Cauca province and highlights the need for further research on the subject in order to propose more pertinent strategies for tick control.…”
Section: Discussionmentioning
confidence: 99%
“…Economic losses caused by ticks in Colombia, as reported by Garcia in 1983, were $5,000 million COP (equivalent to $1.6 million USD) without taking into account the cost of treatments (PolancoEcheverry and Rios-Osorio, 2016). Furthermore, there are reports of tick resistance to acaricides including organochlorines, formamidines, organophosphates, synthetic pyrethroids, and ivermectin (Benavides et al, 2000;Abbas et al, 2014;Araque et al, 2014;Villar et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The LIT with ivermectin was conducted as described previously (Villar et al ., ). A control solution containing 1% ethanol and 0.02% Triton X‐100 in distilled water was used to prepare all immersion dilutions and to test control larvae.…”
Section: Methodsmentioning
confidence: 97%
“…The traditional method of control used throughout the country has been the application of injectable and topical chemical acaricides. However, recent in vivo and in vitro studies conducted across the country have revealed widespread resistance to most commercial acaricides (López‐Arias et al ., ; Puerta et al ., ; Villar et al ., , ). The findings have revealed that pyrethroids, in particular cypermethrin and deltamethrin, are no longer effective in Colombia and most farmers have now abandoned their use for tick control.…”
Section: Introductionmentioning
confidence: 99%